New data on fish diet and bone digestion of the Eurasian otter (Lutra lutra) (Mammalia: Mustelidae) in central France. Issue 1 (1st January 2017) - Guillaud, E.; Bearez, P.; Denys, C.; Raimond, S.
Abstract: Fish remains are abundant and easily recognizable in many archaeological sites. The origin of such assemblages is generally poorly known. The ability to create small fish bone accumulations is restricted to a small number of predators (including raptors, carnivores and humans). In order to recognize the agents responsible for these concentrations in archaeological sites, we have investigated the taphonomy of the fish remains from otter spraints to determine the potential role of the Eurasian otter, Lutra lutra, in the formation of fossil assemblages as a piscivorous mammal. Currently, few data are available to characterize the accumulation of otter remains in natural or archaeological sites. We analyzed a collection of 29 otter spraints from Bugeat (CorrÃ¨ze) in central France. We identified the remains of eight fish species: brown trout ( Salmo trutta, Salmonidae), perch ( Perca fluviatilis, Percidae), pumpkinseed ( Lepomis gibbosus, Centrarchidae), and several Cyprinidae, rudd ( Scardinius erythrophthalmus ), minnow ( Phoxinus phoxinus ), bullhead ( Cottus gobio ), and the indeterminate pair chub/dace ( Squalius cephalus / Leuciscus leuciscus ). The species and the body parts present, along with the reconstruction of the fish weight and observations of any modifications, such as deformation, rounding and polishing, give us insight into otter prey categories and their transformation after digestion. Among the ca. 200 bones constituting the whole fish skeleton, only between six and 39 bones survived depending on the different species. Cyprinids display a high-moderate digestion grade and seem to be the taxon most affected by digestion (64.67%). Based on surface modifications, such as breakage and digestion traces, as well as bone element representation, we produced a set of criteria as a new tool to be applied to the fossil record.